The Low Opportunity Costs of the Amazon Soy Moratorium - Rausch, Lisa L.; Gibbs, Holly K. (Frontiers in Forests and Global Change, 2021)
• Brazil’s Amazon Soy Moratorium (ASM) contributed to overall reductions in Amazon deforestation since its implementation in 2006. • Under the ASM, the Amazon soy sector maintains access to the growing share of the market that operates under zero-deforestation commitments. • The ASM has been criticized as unfair to law-abiding producers. • Only 1% of the approximately 14,000 soy farms in the Amazon Biome have soy-suitable, forested areas that could be deforested lawfully (49,273 ha). • More than half of Amazon soy farms have soy-suitable areas that were deforested before 2008 and used for soy in 2019 (1.7 Mha). • Taken together, these findings suggest that the opportunity costs of the ASM on current soy farms are low relative to the market access benefits.